Outro modernismo em Minas: a trajetória marginal de Inimá de Paula - Julio Cesar Martins (2011)
This dissertation´s theme is to analyze the work of painter Inimá de Paula (1918-1999) from Minas Gerais in historical perspective, under the hypothesis of locate his trajectory in the margins of the history of modernism in Minas Gerais, written centered on painter/teacher Alberto da Veiga Guignard and his disciples. Inimá has participated in the dissemination and implementation of brazilian modernism in Ceará and Rio de Janeiro in the 1940´s and 50´s before returning to Minas Gerais in the mid-60´s where he consolidated his career. The trajectory of the artist testify of an atypical and discreet way in the brazilian art history, which constitutes an instigating and provocative source of innovative interpretations in historical and critical terms of artistic modernity in Brazil.